Determination of piezo-electric fields in spontaneously ordered InGaAsP - Malzer, Stefan; et al. (PHYSICS OF SEMICONDUCTORS: 27th International Conference on the Physics of Semiconductors, ICPS-27, 2005)
We report on observation of a piezo-electric field in InGaAsP-QWs embedded in InP induced by the spontaneous ordering of the MOCVD-grown InGaAsP-layer. The structure was embedded in the intrinsic layer of a p-i-n diode allowing for the internal field determination by the quantum confined Stark effect in photocurrent spectroscopy. The sign and magnitude of this piezo field was determined to 80±2 kV/cm for an In Ga As P /InP layer system. © 2005 American Institute of Physics.